Modelling the impact of Information and Communication Technology (ICT) trade, economic complexity and energy structure on carbon neutrality: Evidence from BRICS - Singh, Neharika; Gupta, Meenakshi (Universitas Islam Indonesia, 2026)
Purpose — This study investigates the impact of Information and Communication Technology (ICT) trade flow components, specifically ICT service exports, ICT goods exports, and ICT goods imports, alongside economic complexity and renewable energy share on carbon emissions.Methodology — A panel of BRICS countries from 2000 to 2022 is estimated using a second-generation cross-sectional autoregressive distributed lag (CS-ARDL) model that accounts for cross-sectional dependence and slope heterogeneity across countries. Findings — Gross domestic product per capita and economic complexity are positively associated with carbon emissions. ICT trade flows have heterogeneous effects on emissions. ICT services, exports, and renewable energy consumption significantly reduce carbon emissions. However, ICT goods exports and imports have an insignificant effect on carbon emissions.Implications — The results suggest that the BRICS countries must emphasise policy measures that promote the export of ICT services, accelerate renewable energy adoption, and promote industrial transformation policies towards sustainable production practices.Originality — This study focuses on supply-side ICT trade channels and disaggregates them into ICT goods exports, imports, and service exports. Furthermore, this study applies second-generation estimation techniques that are robust to cross-sectional dependence and slope heterogeneity